Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

It's an old question, may be from 7th grade, but I am really looking for a good explanation for this question:

A says to B, "I am three times as old as you were, when I was as old as you are". If the sum of their present ages is 64, find the ages of A and B respectively.

share|cite|improve this question
up vote 2 down vote accepted

Let $x$ be the age of A, $y$ the age of B. We know that $x+y=64$, and the sentence "I (A) am three times as old as you (B) were, when I was as old as you are" can be translated as: $3(y - (x - y)) = x$. Thus $y = \frac{2}{3}x$ and we get $x = \frac{3\cdot64}{5} = 38.4$ and $y=\frac{128}{5} = 25.6$.

share|cite|improve this answer
In that kind of riddle, the answer lives surely in $\mathbb N$. – Damien L Feb 4 '13 at 11:29
Hey your method is correct! I have made a change in the question by reducing the sum of the ages to be 60. – Hemant Feb 4 '13 at 11:57
@DamienL: Yes, I know, I was kind of unsure, too. But the method is correct and the answer is right, so... – Daniel Robert-Nicoud Feb 4 '13 at 21:30

Let $x$ be the current age of A and $y$ the current age of B. When A was as old as B now, that was $x - y$ years ago and B's age that time is $y - (x - y)$, which can be simplified as $2y -x$. Now, the statement "I am three times as old as you were, when I was as old as you are" can now be represented by the following expression:

$$x = 3(2y - x)$$

$$x = 6y - 3x$$

$$4x = 6y$$

Since $x + y = 60$, then $y = 60 - x$. So now we have,

$$4x = 6(60 - x)$$

$$4x = 360 - 6x$$

$$10x = 360$$

$$x = 36$$

$$y = 60 - 36 = 24$$

share|cite|improve this answer

The current time will be denoted as $t$. The age of $A$ at time $t$ will be $A(t)$ and the age of $B$ at the same time is $B(t)$. There exists $n$ such that $A(t) = B(t) + n$, $n$ is just the age difference.

Now for any past time $t_0$, we still have $A(t_0) = B(t_0) + n$.

The sentence says that $A(t) = 3 B(t_0)$ where $t_0$ is chosen so that $A(t_0) = B(t)$.

After so equations, you end up with $B(t) = \frac{n}{2}$ and $A(t) = n + \frac{n}{2}$. Knowing the sum is equal to 64, you find that

$$ A(t) = 48 \text{ and } B(t) = 16$$

share|cite|improve this answer
You seem to have a sign issue here - when $A$ was $16$, $B$ was $-16$, thus $A$ should now be $-48$. – Matthew Pressland Feb 4 '13 at 11:55
@ Damien L: This is not the correct answer. I Have made a change in the question, please try with the new age. – Hemant Feb 4 '13 at 11:58

The present ages of A and B are $36$ and $24$ respectively. and the number of years ago in the question is $12$ years (value of $n$)


Let the present ages of A and B be $x$ and $y$.

$n$ years back the ages of A and B are $x-n$ and $y-n$

Given $x = 3(y-n)$ --> "I am three times as old as you were"

$x-n = y$ --> "when I was as old as you are"

Also given $x+y = 60$

Solving these equations will give the above results.

share|cite|improve this answer
May I know if my answer is correct? – Santosh Rao Oct 21 '13 at 5:06

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.